2023
DOI: 10.7717/peerj-cs.1417
|View full text |Cite
|
Sign up to set email alerts
|

Application of public emotion feature extraction algorithm based on social media communication in public opinion analysis of natural disasters

Shanshan Li,
Xiaoling Sun

Abstract: Natural disasters are usually sudden and unpredictable, so it is too difficult to infer them. Reducing the impact of sudden natural disasters on the economy and society is a very effective method to control public opinion about disasters and reconstruct them after disasters through social media. Thus, we propose a public sentiment feature extraction method by social media transmission to realize the intelligent analysis of natural disaster public opinion. Firstly, we offer a public opinion analysis method base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This category includes studies focusing on analyzing public sentiment and perceptions towards disasters or crisis situations. The research works in [19,[41][42][43][44][45] fall within this category, as shown in Table 5 (detailed in Appendix A, Table A2). Notably, models such as BERT demonstrate remarkable accuracy in classifying sentiments towards COVID-19 vaccines and reporting symptoms, leveraging contextual embeddings for nuanced understanding [19,42].…”
Section: Sentiment Analysis and Public Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…This category includes studies focusing on analyzing public sentiment and perceptions towards disasters or crisis situations. The research works in [19,[41][42][43][44][45] fall within this category, as shown in Table 5 (detailed in Appendix A, Table A2). Notably, models such as BERT demonstrate remarkable accuracy in classifying sentiments towards COVID-19 vaccines and reporting symptoms, leveraging contextual embeddings for nuanced understanding [19,42].…”
Section: Sentiment Analysis and Public Perceptionmentioning
confidence: 99%
“…However, challenges such as lower performance exhibited by fixed embeddings, as evidenced by Word2Vec, underscore the importance of employing adaptable models to capture the contextual nuances effectively [42]. Deep Learning [19,41,44] High accuracy in detecting beliefs, opinions, and emotions, showcasing effective analysis.…”
Section: Sentiment Analysis and Public Perceptionmentioning
confidence: 99%